Impact of a training program on the surveillance of Clostridioides difficile infection. (2019) - Sopena, N.; Freixas, N.; Bella, F.; Pérez, J.; Hornero, A.; Limon, E.; Gudiol, F.; Pujol, M.; ,
Abstract: A high degree of vigilance and appropriate diagnostic methods are required to detect Clostridioides difficile infection (CDI). We studied the effectiveness of a multimodal training program for improving CDI surveillance and prevention. Between 2011 and 2016, this program was made available to healthcare staff of acute care hospitals in Catalonia. The program included an online course, two face-to-face workshops and dissemination of recommendations on prevention and diagnosis. Adherence to the recommendations was evaluated through surveys administered to the infection control teams at the 38 participating hospitals. The incidence of CDI increased from 2.20 cases/10 000 patient-days in 2011 to 3.41 in 2016 ( P < 0.001). The number of hospitals that applied an optimal diagnostic algorithm rose from 32.0% to 71.1% ( P = 0.002). Hospitals that applied an optimal diagnostic algorithm reported a higher overall incidence of CDI (3.62 vs. 1.92, P < 0.001), and hospitals that were more active in searching for cases reported higher rates of hospital-acquired CDI (1.76 vs. 0.84, P < 0.001). The results suggest that the application of a multimodal training strategy was associated with a significant rise in the reporting of CDI, as well as with an increase in the application of the optimal diagnostic algorithm.